Salivary Afternoon Cortisol and Relationship Status in Healthy Women With Regular Menstrual Cycles. Issue 3 (3rd July 2018) - Wilson, M. Claire; Lorenz, Tierney K.; Heiman, Julia R.
Abstract: Although ovarian hormones and social relationships are known to interact with HPA axis regulation, evidence for systematic covariation with basal salivary cortisol levels remains mixed. As part of a larger study, in this analysis we pursued two questions. First, do baseline cortisol concentrations consistently vary across the menstrual cycle? Second, do cortisol levels differ by relationship status? We collected afternoon saliva samples at four points across the menstrual cycle from 14 single and 18 monogamously partnered women, ages 18 to 48, who were not taking hormonal medications. Samples taken in the lab yielded significantly higher cortisol concentrations than samples provided at home; the two were thus considered separately. No significant differences were observed across lab-session (menses vs. ovulation) or at-home (follicular vs. luteal) levels. This finding converges with studies of awakening salivary, urinary, and plasma cortisol, which suggest that, in healthy women, menstrual schedules do not affect systematic shifts in basal cortisol. Contrary to expectations, single and partnered women did not differ in overall cortisol levels. Future research would benefit from examining potential links between cortisol, relationship status, and sexual activity.